Tobacco Root Microbial Community Composition Significantly Associated With Root-Knot Nematode Infections: Dynamic Changes in Microbiota and Growth Stage - Cao, Yi; Yang, Zhi-Xiao; Yang, Dong-Mei; Lu, Ning; Yu, Shi-Zhou; Meng, Jian-Yu; Chen, Xing-Jiang (Frontiers in Microbiology, 2022)
The root-knot nematode (RKN) is an important pathogen that affects the growth of many crops. Exploring the interaction of biocontrol bacteria-pathogens-host root microbes is the theoretical basis for improving colonization and controlling the effect of biocontrol bacteria in the rhizosphere. Therefore, 16S and 18S rRNA sequencing technology was used to explore the microbial composition and diversity of tobacco roots (rhizosphere and endophytic) at different growth stages in typical tobacco RKN-infected areas for two consecutive years. We observed that RKN infection changed the α-diversity and microbial composition of root microorganisms and drove the transformation of microorganisms from bacteria to fungi. The abundance of Sphingomonas decreased significantly from 18% to less than 3%, while the abundance of Rhizobiaceae increased from 4% to 15% at the early growth stage during the first planting year, and it promoted the proliferation of Chryseobacterium at the late growth stage in rhizosphere microorganisms with the highest abundance of 17%. The overall trend of rhizosphere microorganisms changed in the early growth stage with increasing growth time. The specific results were as follows: 1. Rhizobiaceae and Chryseobacterium increased rapidly after 75 days, became the main abundant bacteria in the rhizosphere microorganisms. 2. The dominant flora in fungi were Fusarium and Setophoma. 3. Comparing the root microbes in 2017 and 2018, RKN infection significantly promoted the proliferation of Pseudomonas and Setophoma in both the rhizosphere and endophytes during the second year of continuous tobacco planting, increasing the relative abundance of Pseudomonas from 2% to 25%. Pseudomonas was determined to play an important role in plant pest control. Finally, a total of 32 strains of growth-promoting bacteria were screened from tobacco rhizosphere bacteria infected with RKN through a combination of 16S rRNA sequencing and life-promoting tests. The results of this research are helpful for analysing the relationship between root-knot nematodes and bacteria in plants, providing reference data for elucidating the pathogenesis of RKNs and new ideas for the biological control of RKNs.